Practical synthesis of Schollkopf's bis-lactim ether chiral auxiliary: (3S)-3,6-dihydro-2,5-dimethoxy-3-isopropyl-pyrazine - Bull, S; Davies, S; Moss, W (1998)
Practical methodology for the bis-O-methylation of (3S)-isopropyl-piperazine-2,5-dione 4 on a 45 g scale to generate Schollkopf's bis-lactim ether chiral auxiliary (3S)-3,6-dihydro-2,5-dimethoxy-3-isopropyl-pyrazine 1 has been developed. Monomethylated intermediates 5 and 6 are reported for the first time. The gelling effects of 4 in a range of common solvents are also described.